Economic Value in the Bejuli Tradition of Kuang Dalam Malay Community - Aravik, Havis (Jurnal Studi Islam Indonesia (JSII), 2024)
Every tradition in society not only has social and cultural values but also economic values. The Bejuli tradition of the Kuang Dalam Malay community is no exception. This research will discuss this with the aim of knowing the economic value of the Bejuli tradition of the Kuang Dalam Malay Community. This research uses a qualitative method with a data collection model through observation and interviews with stakeholders. The result of this research is that the Bejuli tradition in the Kuang Dalam Malay community not only has high cultural value, but also has a significant economic impact. This tradition creates business opportunities for local craftsmen, especially in the manufacture of tandu juli, traditional clothing, and various traditional knick-knacks used in the wedding procession. However, there is a downside to this tradition. The high cost of traditional clothing such as ‘Aesan Gede’, musical accompaniment, and the meal after the Bejuli procession can be an economic burden for poor families. .